Reactions to Environmental Changes: Place Attachment Predicts Interest in Earth Observation Data - Wullenkord, Marlis Charlotte; Heidbreder, Lea Marie; Reese, Gerhard (Frontiers in Psychology, 2020)
Environmental changes such as extreme weather events become increasingly noticeable worldwide. Earth observation data provide information about such changes, but little is known about citizens’ perceptions of and responses to such changes. Across three studies, we assess whether people’s place attachment on different regional levels predicts interest in earth observation data, and whether perceived environmental change affects emotional responses and place attachment. Two survey studies (N=118 students and N=197 citizens from region blinded for review) revealed that place attachment predicts interest in earth observation data, especially when people felt strongly attached to the region or place in question. A third experimental study (N=600) with repeated measures (N=203) revealed that visualized environmental change – using satellite images of local vs. non-local environmental change – did not affect place attachment but elicited stronger emotional responses than visualizing no change. Policy support measures across Studies 2 and 3 suggest that place attachment and emotional responses are important predictors for action to mitigate consequences of environmental change.